Un Algoritmo Evolutivo para la Solución de Problemas en Marketing (2015)
This work of investigation is to develop a solution to three problems in the work area of marketing that are modeled by combinatorial optimization. Through the development of a framework and building a toolbox in Matlab, implementing the meta-heuristic EPSO "Evolutionary Swarm Optimization particles." The TDPs is to determine a division of a set of units located in a territory that meets multiple criteria such as compactness, connectivity and balance in terms of customer and product demand. The PLDP consist in determine the specific attribute levels for each multiattribute product in a set of products to maximize the resulting product line’s share of choice, and the VRPSPD resolve problem the determine the vehicle fleet for minimize the sum of travel time with the restriction the vehicle must have enough capacity for transporting the commodities to the delivered and those ones picked-up customers and returning depot. All problems constituting an important support that should not be ignored by those responsible for the activities related to the commercial area as it becomes a tactical decision for the company.